2011
DOI: 10.1089/jwh.2010.2303
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and Polycystic Ovary Syndrome

Abstract: Background: Polycystic ovary syndrome (PCOS) is a common metabolic-endocrine disorder in women and is associated with a number of metabolic morbidities. We examined the association of PCOS and its components with socioeconomic status (SES) over the life course to explore the role of the environment on the development of PCOS. Conclusions:Our results indicate that women who experienced low childhood SES are at increased risk of PCOS, but this risk is limited to those who have personally attained a high level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 44 publications
8
51
0
2
Order By: Relevance
“…Furthermore, a study carried out in Brazil [40] confirms that schooling is associated with greater care in reproductive life, later sexual debut and fewer children, possibly explaining part of the effect found in the present study. Exploring socioeconomic status in women with PCOS, Merkin et al recently found that the risk of the syndrome and its components is higher in the presence of a combined effect of poor parental education/high personal education [41]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study carried out in Brazil [40] confirms that schooling is associated with greater care in reproductive life, later sexual debut and fewer children, possibly explaining part of the effect found in the present study. Exploring socioeconomic status in women with PCOS, Merkin et al recently found that the risk of the syndrome and its components is higher in the presence of a combined effect of poor parental education/high personal education [41]. …”
Section: Discussionmentioning
confidence: 99%
“…We utilized data from the CARDIA cohort (11,12), and the CARDIA Women’s Study (CWS) (13,14), an ancillary study to CARDIA. The CARDIA cohort is a multicenter community-based longitudinal study of cardiovascular disease in young African American and Caucasian adults aged 18–30 years.…”
Section: Methodsmentioning
confidence: 99%
“…The research suggests that education and income play a role in the development of PCOS across the life course. For instance, low socioeconomic status in childhood (measured by parental education) has been found to increase the risk of PCOS in adulthood (measured by educational level), particularly among obese women with high socioeconomic status in adulthood 55. Additionally, symptoms of PCOS such as anovulation (ie, menstrual problems) can differ according to socioeconomic status, and these differences are associated with clinical and endocrine factors.…”
Section: Life Course Perspective and Study Of Pcosmentioning
confidence: 99%